Foreign Location Choice: Review and Extensions. (8th April 2015) - Kim, Jin Uk; Aguilera, Ruth V.
Abstract : International Business (IB) research on foreign‐location choice has experienced a revival in recent years, yet a comprehensive review has been sorely lacking. The purpose of this review is to synthesize the findings of recently published articles on the topic of foreign‐location choice and offer fruitful directions for future research. This review consists of three sections: first, the authors provide a historical overview of this research stream by tracing its origins and analyzing the general trend that has shaped research on foreign‐location choice. Next, the authors conduct a review of 137 recent articles published in leading IB and business/management journals. These articles are categorized according to common topics, and the main findings of each category are synthesized in order to bring some cohesion to this fragmented field. Lastly, the authors identify issues that remain under‐researched or require re‐thinking some taken‐for‐granted assumptions. Through this effort, they are able to connect the past, present and future of research on foreign‐location choice and to shed some new light on the IB literature.